Bilateral cellular flows display asymmetry prior to left–right organizer formation in amniote gastrulation - Rieko Asai; Shubham Sinha; Vivek N. Prakash; Takashi Mikawa (Proceedings of the National Academy of Sciences, 2025)
A bilateral body plan is predominant throughout the animal kingdom. Bilaterality of amniote embryos becomes recognizable as midline morphogenesis begins at gastrulation, bisecting an embryonic field into the left and right sides, and left–right (LR) asymmetry patterning follows. While a series of laterality genes expressed after the LR compartmentalization has been extensively studied, the laterality patterning prior to and at the initiation of midline morphogenesis has remained unclear. Here, through a biophysical quantification in a high spatial and temporal resolution, applied to a chick model system, we show that a large-scale bilateral counterrotating cellular flow, termed “polonaise movements”, display LR asymmetries in early gastrulation. This cell movement starts prior to the formation of the primitive streak (PS) (the earliest midline structure) and the subsequent appearance of Hensen’s node (the LR organizer). The cellular flow speed and vorticity unravel the location and timing of the LR asymmetries. The bilateral flows displayed a Right dominance after 6 h since the start of cell movements. Mitotic arrest that diminishes PS formation resulted in changes in the bilateral flow pattern, but the Right dominance persisted. Our data indicate that the LR asymmetry in amniote gastrula becomes detectable earlier than suggested by current models, which assume that the asymmetric regulation of the laterality signals at the node leads to the LR patterning. More broadly, our results suggest that physical processes can play an unexpected but significant role in influencing LR laterality during embryonic development.